Holding Back the Tears: Individual Differences in Adult Crying Proneness Reflect Attachment Orientation and Attitudes to Crying - Millings, Abigail; Hepper, Erica G.; Hart, Claire M.; Swift, Louise; Rowe, Angela C. (Frontiers in Psychology, 2016)
Despite being a universal human attachment behavior, little is known about individual differences in crying. To facilitate such examination we first recommend shortened versions of the attitudes and proneness sections of the Adult Crying Inventory using two independent samples. Importantly, we examine attachment orientation differences in crying proneness and test the mediating role of attitudes toward crying in this relationship. Participants (Sample 1 N=623, Sample 2 N=781), completed online measures of adult attachment dimensions (avoidance and anxiety), attitudes towards crying, and crying proneness. Exploratory factor analyses in Sample 1 revealed four factors for crying attitudes: crying helps one feel better; crying is healthy; hatred of crying; and crying is controllable; and three factors for crying proneness: threat to self; sadness; and joy. Confirmatory factor analyses in Sample 2 replicated these structures. Theoretically and statistically justified short forms of each scale were created. Multiple mediation analyses revealed similar patterns of results across the two samples, with the attitudes ‘crying is healthy’ and ‘crying is controllable’ consistently mediating the positive links between attachment anxiety and crying proneness, and the negative links between attachment avoidance and crying proneness. Results are discussed in relation to attachment and emotion regulation literature.